Sequential inflammatory response of fingerlings of Indian major carps to Aphanomyces invadans - Pradhan, P K; Mohan, C V; Shankar, K M; Kumar, B Mohana (Indian Journal of Fisheries, 2011)
The present paper describes the sequential inflammatory response of fingerlings of Indian major carps (IMC) to experimental infection of the fungal pathogen, Aphanomyces invadans. In all the three species of IMC, at one day of post injection (dpi), few fungal hyphae penetrating the musclefibres were observed in the lesion area but no inflammatory response was found at the site. At 2 dpi, numbers of hyphae in the lesion increased and there was extensive infiltration ofinflammatory cells. At 4 dpi, the mycotic lesion spread in the musculature at the site of injection and the lesion further extended even to the non-injected lateral side of the body. The fungal hyphae at the central part of the lesion were encapsulated by macrophages and/or epithelioid cells forming granulomata. At 6 dpi, both injected and non-injected sides and most of the internal organs revealed extensive mycotic lesions. There was extensive myonecrosis in large areas of myotome